PROFIL MOTIVASI BELAJAR SISWA KELAS XI SMA GUNUNG HALU - Nirmala Chandra Anggraenie; Euis Eti Rohaeti; Tuti Alawiyah (IKIP Siliwangi, 2021)
The purpose of this study was to describe the learning motivation of class XI students at SMAN 1 Gunung Halu. The study participants consisted of 15 students who had low learning motivation. This study uses a quantitative descriptive research method, where data collection is through observation, interviews and questionnaires. The results of the research from the distribution of the student learning motivation score questionnaire showed that most of the students were still classified as moderate at 51.09% where students get bored quickly when getting assignments, 54.53% on student resilience when facing problems and 56.88% of children are less able to defend their opinions . Based on this data, it can be concluded that student learning motivation still needs to be improved by changing teaching methods to be more varied and innovative so that students do not feel bored. It is also hoped that students will be more active and enthusiastic in accepting, looking for and meeting new things in lessons.Keywords: motivation learning, students